(untitled) (Latakia University Journal -Medical Sciences Series, 2023)
Aspirin is marketed by Bayer as a brand drug with a high cost, and many generic drugs for it are available in Syrian pharmaceutical market with a low price. For the possibility of interchangeability between them, a bioequivalence test must be evaluated, which is a prerequisite for switching between a brand and a generic drug, whether in vivo or in vitro. Because of the ethical aspect and the too high cost of in vivo studies, the concept of IVIVC (In Vitro- In Vivo Correlation) is resorted to, which allows to study of only drugs that achieve it only in vitro, including aspirin. This study aims to evaluate the in vitro bioequivalence of aspirin tablets and capsules available in the Syrian market. Quality control tests (weight and content uniformity, mechanical resistance, disintegration time), and dissolution test for tablets (A, B, C) were performed and compared with the brand drug (P). Weight, content uniformity and dissolution tests for capsule (D, E) were performed, and comparison between them. The dissolution profiles were compared using of similarity and difference factor (f1 & f2). All batches achieved the test of uniformity of (weight and content), friability and disintegration time values were agreed with the pharmacopoeia requirements. for the dissolution test, all tablets released more than 75% in 90 minutes. for capsules only the D2 released more than 80 % in 90 min. By calculating (fi & f2), it was found that all tablets were not bioequivalent to the brand drug and cannot interchangeable with it.